From the Love of Liberty to the Cult of Might: Continuities and Discontinuities Between Liberalism and Fascism - León, Sebastián (2024)
In the following essay, we will seek to explore the ties of kinship between liberalism and fascism, both in their ideas and in their concrete political practice, with the intention of, through the contrast, shedding some light on the category of fascism. In the first part, we will consider the category of totalitarianism, so widespread in the political imagination that seeks to understand fascism, and why we find it of little use to think about this political phenomenon; in the second, we will take a tour of the ideas and practice of liberalism, relying largely on its historical genealogy prepared by the Marxist philosopher and historian Domenico Losurdo, who directly links the emergence of liberalism to modern colonialism; finally, in the third part, we will return to the category of fascism, to review its characteristics, and verify to what extent the history and practice of the liberal tradition allows us to shed light on it.